Gambaran Perhatian Orang Tua pada Remaja yang Kecanduan Bermain Games Online - Yumia Mudi Sari; Vevi Sunarti (RC-INSTITUT, 2020)
This study is motivated by high teenage learning results addicted to play online games in Kuranji Hilir, Sungai Limau Sub-district of Padang Pariaman Regency. This is due to the attention given by parents to teenagers. This study aims to describe the attention of parents in teenagers who are addicted to playing online games in Kuranji Hilir, Sungai Limau Sub-district of Padang Pariaman Regency seen from the aspects of guidance and advice, supervision, punishment, and award, communicating, and regulate playtime. The approach used in this study uses quantitative descriptive techniques. The population of this research is a teenager who is addicted to play online games in Kuranji Hilir, Sungai Limau Sub-district of Padang Pariaman Regency as many as 60 people, and samples taken by using Stativeed Random Sampling technique as much as 36 people. Data collection techniques use questionnaires with data collection tools to use questionnaires and data analyzed by percentage techniques. The results of this study indicate that based on aspects of the overall parent's attention look very well. This is evidenced by the many teenagers who provide alternative answers always and often. Based on the results of this study, it is expected to parents to maintain and increase attention to children to grow and development of children can be awake according to the desired, and expected to children to control itself in playing online games so as not to interfere with other activities such as learning, rest and so on.